The Challenges Faced by UPT SD Negeri 197 Gresik to Build a Culture of Interest in Reading in Students - Anggun Dea Pitaloka (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia is a developing country in Southeast Asia. Indonesia is predicted to want to become a developed country. One indicator of a developed country is a high literacy rate, but in Indonesia the level of interest in reading is still low. Increasing the level of interest in reading in Indonesia can be done by increasing reading activities. However, it is very unfortunate that even reading interest in Indonesia is still low. So there is a need for improvement in this matter for the future of Indonesia